2014
DOI: 10.1063/1.4882283
|View full text |Cite
|
Sign up to set email alerts
|

Striking role of non-bridging oxygen on glass transition temperature of calcium aluminosilicate glass-formers

Abstract: Molecular dynamics simulations are used to study the structural and dynamic properties of calcium aluminosilicate, (CaO-Al2O3)1-x(SiO2)x, glass formers along three joins, namely, R = 1, 1.57, and 3, in which the silica content x can vary from 0 to 1. For all compositions, we determined the glass-transition temperature, the abundances of the non-bridging oxygen, triclusters, and AlO5 structural units, as well as the fragility from the temperature evolution of the α-relaxation times. We clearly evidence the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…Additional static DFT calculation were performed to determine the temperature evolution of C P within the lattice dynamics theory 37 in the crystalline states at low temperatures. Classical MD were performed using a BMH empirical potential [31][32][33] to determine the temperature evolution of the enthalpy, constant pressure specific heat as well as the melting temperature and related enthalpy of fusion. Our findings indicate that the empirical Born-Mayer-Huggins potential used [31][32][33] gives an adequate representation of pure CaO in the liquid and solid states as compared to available experimental data and DFT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional static DFT calculation were performed to determine the temperature evolution of C P within the lattice dynamics theory 37 in the crystalline states at low temperatures. Classical MD were performed using a BMH empirical potential [31][32][33] to determine the temperature evolution of the enthalpy, constant pressure specific heat as well as the melting temperature and related enthalpy of fusion. Our findings indicate that the empirical Born-Mayer-Huggins potential used [31][32][33] gives an adequate representation of pure CaO in the liquid and solid states as compared to available experimental data and DFT.…”
Section: Introductionmentioning
confidence: 99%
“…Classical MD were performed using a BMH empirical potential [31][32][33] to determine the temperature evolution of the enthalpy, constant pressure specific heat as well as the melting temperature and related enthalpy of fusion. Our findings indicate that the empirical Born-Mayer-Huggins potential used [31][32][33] gives an adequate representation of pure CaO in the liquid and solid states as compared to available experimental data and DFT. The present methodology and theoretical results provide an new accurate basis for thermodynamic calculations, and results are discussed within the calculation of phase diagrams 39 (CALPHAD) framework.…”
Section: Introductionmentioning
confidence: 99%
“…1 Ternary phase diagram for the CaO-Al 2 O 3 -SiO 2 system highlighting the different regions where a given oxide component crystallizes from the corresponding melt. 56 It was also confirmed that the Al distribution in simulated CAS glasses follows Loewenstein's rule (or Al avoidance principle, valid for low Al content). The labels and points in red correspond to the clinker crystalline phases modeled by the present force-field.…”
Section: Evaluation Of the Lennard-jones Interatomic Potential Paramementioning
confidence: 66%
“…3a). Previous studies 53 demonstrated an increase in Al-coordination as a function of hardness and densification. Based on the residual density profiles, in Figure 4, and the Al (V) coordination in Figure 5, it is likely the increased coordination state plays a dominant role in the densification and crosslinking of the glass network.…”
Section: Coordination Number Distributionmentioning
confidence: 83%
“…Considering the kinetic fragility index, which characterizes how rapidly the relaxation process occurs, we anticipate fragility to increase with larger initial densities 52 . As a result, glasses with high silica concentration (and lower initial density) are more difficult to relax 53 . Highly localized heating from the pulse-glass interaction produces the largest distribution in density profiles for these glasses.…”
Section: Residual Density Profilementioning
confidence: 99%